The effects of lifting lighter and heavier loads on subjective measures - Emanuel, A.; Smukas, I. I. R.; Halperin, I. (International Journal of Sports Physiology and Performance, 2021)
Background: Despite the progress made in the study of subjective measures in resistance training, some questions remain unanswered. Here the authors investigated if ratings of perceived exertion (RPE) can predict task failure and bar velocity across exercises and loads as a primary outcome and whether a battery of subjective measures differ as a function of the lifted loads as a secondary outcome. Methods: In this preregistered study, 20 resistance-trained subjects (50% female) first completed a 1-repetition-maximum test of the barbell squat and bench press. In the second and third sessions, they completed 2 sets of squats followed by 2 sets of bench press to task failure, using 70% or 83% of 1-repetition maximum, while bar velocity was recorded. RPE scores were recorded after every repetition. In addition to RPE, rating of fatigue, affective valence, enjoyment, and load preferences were collected after set and session completion. Results: Across conditions, RPE was strongly correlated with reaching task failure (r = .86) and moderately correlated with bar velocity (r = -.58). The model indicates that an increase in 1 RPE unit is associated with an 11% shift toward task failure and a 4% reduction in bar velocity, with steeper slopes observed in the heavier condition. Negligible differences were observed between the load conditions in rating of fatigue, affective valence, enjoyment, and load preference. Conclusion: RPE scores, collected on a repetition-by-repetition basis, accurately reflected reaching task failure across loads and conditions. Hence, RPE can be used to prescribe repetition numbers during ongoing sets. The negligible differences between load conditions in rating of fatigue, affective valence, enjoyment, and load preference indicate that when sets are taken to task failure, loads can be selected based on individual preferences.